Impact of small scale dairy farming projects on rural livelihoods: the case of Mayfield Dairy Settlement Scheme in Chipinge district of Zimbabwe - Hahlani, Crispen D.; Garwi, Jabulani (Midlands State University, 2016)
Rural livelihood diversification and agricultural intensification are key pathways to sustainable rural livelihoods. Most less developed economies have adopted smallholder dairy farming as a doublebarreled strategy for achieving both rural livelihood diversification and agricultural intensification. This study sought to assesses the impact of dairy farming projects on rural livelihoods. In this study, focus was on Mayfield Small Scale Dairy Settlement Scheme located in Chipinge District of Zimbabwe. In collecting both qualitative and quantitative data, the researchers made use of interviews, questionnaires, observations and project reports. Semi-structured questionnaires were administered to a sample of 75 farmers randomly selected from a total population of 345 family farmers operating on the dairy settlement scheme. In addition, 24 key informants were conveniently sampled for interviews from among the scheme’s management, farmer committee leaders and extension workers. The major finding in the study was that while it managed to bring about a number of benefits to the smallholder family farmers, the project, however, failed to provide a solid basis for sustainable rural livelihoods in the project area. Lack of a proper ‘fit’ between project design, beneficiary needs and the capacities of the assisting organizations was the major reason behind the project’s lackluster performance.